Clinical and echocardiographic predictors of delirium in acute cardiac care unit after transfemoral aortic valve implantation. (26th April 2021) - Noriega, F; Viana-Tejedor, A; Luque, T; Travieso, A; Corrochano, D; Mcinerney, A; Ferrera, C; Tirado-Conte, G; Jimenez-Quevedo, P; Nunez-Gil, I; Gonzalo, N; Agustin, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Delirium is frequent in patients admitted to critical care units. Its incidence after transcatheter aortic valve implantation (TAVI) is up to 30%. Clinical and demographic factors have been related to delirium, but echocardiographic parameters have not been evaluated. Purpose. The aim of this study was to assess clinical and echocardiographic predictors of delirium in patients admitted to an acute cardiac care unit (ACCU) after transfemoral TAVI. Methods. 501 patients admitted to ACCU after TAVI were included. Delirium was evaluated by Confusion Assessment Method. Clinical cardiovascular and geriatric conditions were assessed, as well as echocardiographic parameters. Results. The incidence of delirium was 22% (110 patients). Delirium was associated with age (83.8 ± 4.6 vs 82.6 ± 6.1 years, p = 0.026), dyslipidaemia (50.0% vs 61.4%, p = 0.032), prior peripheral arterial disease (11.9% vs 5.4%, p = 0.017) and cognitive impairment (10.0% vs 1.8%, p < 0.001). There was no relationship to gender, other cardiovascular risk factors or geriatric conditions. Table shows echocardiographic parameters at baseline and after TAVI, with no statistical association with delirium. Conclusion. Delirium is a common complication after TAVI in ACCU. Age, the absence of dyslipidaemia, or the presence of cognitive impairment or prior peripheral arterial disease are clinical predictors of delirium. There are not echocardiographic predictors of delirium.